Spectrophotometric Determination of Fluorgenic Xanthene Dyes - CHAICHI, M.J.; AZIZI, S.N.; ABEDIRAD, S.M. (Asian Journal of Chemistry, 2010)
In this paper, the change of absorbance and their first and second derivatives for the Xanthene dyes as concentration dependence are reported. The effect of change of smoothing on the LOD and other analytical characteristics are investigated.